A qualitative investigation of expected versus actual initial sexual experiences before age 16. (31st December 2018) - Garceau, Camille; Ronis, Scott T.
ABSTRACT: Introduction: Individuals often develop expectations prior to their initial sexual experiences based on external messages from peers and the broader culture. According to sexual script theory (Simon & Gagnon, 1986), these expectations form schemas about how an initial sexual experience should occur. When reality deviates from these schemas, dissatisfaction can occur (McCormick, 1987). The current study examines the contrast between expectations and reported initial sexual experiences before age 16. Methods: Forty young adult participants were recruited from four local Atlantic Canadian universities (77.5% women; M age = 20.20, SD = 1.31; 75% heterosexual; 77.5% Caucasian). Semi‐structured qualitative interviews on participants' actual initial sexual experiences, expectations of initial sexual experiences, and perceived consequences of initial sexual experiences were conducted. Thematic analysis of the interviews was conducted using a grounded theory framework. Results: Findings indicated that respondents' expectations were influenced by sources such as various media, peers, family, and religion. Initial sexual experiences reportedly met, surpassed, or failed to meet participants' expectations. The presence or absence of a discrepancy between expected and actual sexual experiences was perceived to shape subsequent sexual encounters. A theoretical model of development and adaptations of sexual experience expectations was developed in accordance with these results. Conclusions: Comparisons between expected and actual initial sexual experiences can be perceived by youth as having consequences on their personal and interpersonal well‐being. Honest communication between parents, educators, and youth should therefore be prioritized in order to establish more realistic expectations of initial sexual experiences.